Paying Postage: Estimating the Elasticity of Voter Turnout - Mark Schelker; Marco Schneiter (Center for Economic Studies and ifo Institute (CESifo), 2015)
We aim to estimate the elasticity of voter turnout. We analyze how voters react to a change in voting costs. Some municipalities in the canton of Berne reduced voting costs by paying the postage of the return envelope when voters opt for postal voting. We find that paying the postage is associated with a statistically significant 1.8 percentage point increase in voter turnout. This increase in turnout negatively affects the alignment of voters with leftist party positions.
Keywords: D72; 330; voting cost; postal voting; voter turnout